Code switching Used by Naila on Her YouTube Channel: Naila Farhana - Kadek Yuda Wardana; Luh Putu Laksminy; Made Detriasmita Saientisna (Journal Social and Humaniora, 2021)
Code switching is a phenomenon where a person switches their language when speaking. Code switching or CS is mostly used by young teenager who are able to speak in 2 more languages, or bilingual, and young YouTuber from Indonesia, Naila is one of them. This research aims are to analyzed the types and functions of Code Switching that Naila uttered on one of her YouTube video entitled “Belajar Bahasa Asing OTODIDAK kayak Fiki Naki”. Using qualitative research method and both theories of code switching types by Poplack (1980) and speech function of code switching theories by Appel & Muysken (2005), this research found all the types and functions are used in the video with Intra-sentential code switching and metalinguistic function are the most frequent used by Naila on the video.